PRINCIPAL MANAGEMENT IN THE IMPLEMENTATION OF THE TEACHING FACTORY TO IMPROVE GRADUATES' QUALITY - Sri Wardhani; Saiful Bahri; Munawar Munawar (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2025)
Vocational High Schools are designed to produce work-ready graduates; however, the high unemployment rate among SMK graduates indicates a mismatch between school competencies and labor market demands. Teaching Factory (TEFA) has been developed as a contextual vocational learning approach, yet its implementation continues to face challenges, particularly in managerial aspects. This study aims to describe the principal’s management in improving graduate quality through Teaching Factory-based learning at SMK Negeri 2 Langsa. A qualitative approach was employed, with data collected through interviews, observations, and documentation. Data analysis was conducted using NVivo 12 software. The novelty of this study lies in positioning Teaching Factory as a vocational education management system driven by the principal’s leadership, rather than merely as a learning model, through the integration of four management functions: planning, organizing, implementing, and supervising. The findings indicate that planning is carried out strategically and collaboratively with industry partners, organizing is reflected in the strengthening of work structures and human resources, implementation is conducted through coordination and product-based evaluation, and supervision is adaptive and continuous. The implementation of TEFA management has a significant impact on improving graduate quality, as reflected in the increased graduate absorption rate based on the 2025 Education Report. These findings provide both theoretical and practical contributions to the development of vocational education management at SMK Negeri 2 Langsa.